PERANAN PARTNERSHIPS IN THE ENVIRONMENTAL MANAGEMENT FOR SEAS OF EAST ASIA (PEMSEA) MELALUI PROGRAM INTEGRATED COASTAL MANAGEMENT (ICM) DALAM PENGENDALIAN KERUSAKAN EKOSISTEM TERUMBU KARANG DI INDONESIA - Rizki Rakhmawati (Universitas Komputer Indonesia, 2017)
This study aims to determine the role of the Partnerships in Environmental Management for the Seas of East Asia (PEMSEA) through Integrated Coastal Management Program (ICM) for Controlling the Damages of the Coral Reefs Ecosystem in Palabuhanratu, Sukabumi Regency, West Java. Researcher attempted to analyze the purpose of doing damage control program in coral reef ecosystems that occur in coastal areas Palabuhanratu, Sukabumi Regency, West Java. Author of the research methods used in this study is descriptive analysis method. Most of the datas have been gathered through library research, online data retrieval, documentation, interviews and observation. The results showed that the implementation of ICM in Palabuhanratu, Sukabumi, West Java has involved many sectors related to the management of the Marine and Coastal regions in Palabuhanratu Sukabumi, West Java, with the implementation of several development projects in the coastal region of Palbuhanratu since 2003. But technically still have not made a direct attempt to address the damage to the coral reefs that occur in Palabuhanratu because of the constraints faced. Efforts made in the control of coral reef damage is in the form of outreach to the local community Palabuhanratu coast of Kenya, West Java since 2004.